Pattern of road traffic injuries in the Rethymnon region, Crete, Greece: a secondary hospital-based study - Iraklis Perysinakis; Anastasia Spartinou; Mikela-Rafaella Siligardou; Maria Savvides; Georgios Lianeris; George Stamatakis (James Cook University, 2021)
Introduction: Despite the significant progress that has been made during the last decade, Greece still faces the effects of road traffic accidents (RTAs) to a great extent every year. This study represents an epidemiological approach to road traffic injuries (RTIs) presenting to a secondary hospital in a geographical area with very low-quality road network; it aims to indicate possible preventive measures and actions. Methods: The present study was conducted in Rethymnon General Hospital between January 2018 and February 2020. Data from all trauma patients who presented to the emergency department (ED) after RTAs were retrospectively collected from patient medical records. The severity of injury sustained by road traffic victims was graded using the Injury Severity Score (ISS). Results: During the study period, 1582 trauma patients presented to the ED after RTAs. There were 1079 men and 503 women and the median age was 30 years. In total, 818 motorcycle-related injuries (51.7%), 497 automobile-related injuries (31.4%), 165 bicycle-related injuries (10.4%) and 102 pedestrian injuries (6.4%) were documented. Of the 1582 trauma patients, 58.2% (921) presented with injuries to the extremities, 35.3% (554) presented with thoracic injuries, 34.4% (541) presented with head injuries, 30% (475) presented with spinal column injuries, 17.4% (271) presented with facial injuries, 12.9% (203) presented with abdominal injuries and 10.3% (162) presented with pelvic injuries. A significant increase in the number of incidents was noticed during the tourist season. Median ISS was 2 (IQR=4). 53.7% of patients who were transferred to the hospital by ambulance had an ISS≤4. In 41 cases, transportation to a tertiary hospital was necessary, six patients had emergency operations and 13 others died in the ED. The median length of hospital stay was 3 (IQR=6) days. Conclusion: Actions that could possibly mitigate the burden of RTIs in the district of Rethymnon include upgrading the level of law enforcement, implementing educational strategies and information campaigns against inappropriate ambulance use, encouraging facilities to develop trauma registries and ensuring adequate hospital staffing.